2005
DOI: 10.1182/blood-2004-03-1046
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of nucleoside transporter and metabolism gene expression in chronic lymphocytic leukemia (CLL): identification of fludarabine-sensitive and -insensitive populations

Abstract: Resistance to fludarabine is observed in the clinic, and molecular predictive assays for benefit from chemotherapy are required. Our objective was to determine if expression of nucleoside transport and metabolism genes was associated with response to fludarabine therapy in patients with chronic lymphocytic leukemia (CLL).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
1
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 28 publications
3
68
1
1
Order By: Relevance
“…Furthermore, it has also been described that CLL subjects with elevated hCNT3 expression, a concentrative nucleoside transporter that has been shown to mediate cellular entry of fludarabine, had a lower complete response rate to fludarabine therapy. 13 However, the current study did not show any relationship between response to fludarabine and expression of hCNT3, although it did provide evidence of a positive correlation between mRNA expression of hENT2 and induction of TIGAR, thus supporting the concept that hENT2-related function might determine the transcriptomic response to fludarabine.…”
Section: Discussioncontrasting
confidence: 35%
See 1 more Smart Citation
“…Furthermore, it has also been described that CLL subjects with elevated hCNT3 expression, a concentrative nucleoside transporter that has been shown to mediate cellular entry of fludarabine, had a lower complete response rate to fludarabine therapy. 13 However, the current study did not show any relationship between response to fludarabine and expression of hCNT3, although it did provide evidence of a positive correlation between mRNA expression of hENT2 and induction of TIGAR, thus supporting the concept that hENT2-related function might determine the transcriptomic response to fludarabine.…”
Section: Discussioncontrasting
confidence: 35%
“…11 CLL cells express hENT1, hENT2, hCNT2 and hCNT3 mRNA, although most of the biological activity responsible for fludarabine uptake is associated with hENT transporters. 12 This is probably due to the fact that the hCNT3 protein is localized mostly in intracellular compartments of CLL cells, 13 while fludarabine is not a suitable permeant for hCNT2, 11 a transporter protein that is functional at the plasma membrane of CLL cells. 12 In fact, although both hENT1 and hENT2 can mediate fludarabine internalization, hENT2 but not hENT1 protein levels have recently been correlated with ex vivo sensitivity of CLL cells to this nucleoside analog.…”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent in magnitude and direction with our previous report. 22 In terms of OR rates, there was a trend toward lower On the basis of these findings, we therefore infer that hCNT3 protein has a direct mechanistic role in cellular resistance to F-ara-A, although the underlying mechanisms are not yet fully understood. Although F-ara-A resistance mechanisms may include reduced drug uptake and intracellular drug accumulation, 9 paradoxically we found that it was high, rather than low, hCNT3 IHC staining that correlated with shorter TTP and clinical resistance.…”
Section: Discussionmentioning
confidence: 92%
“…We previously reported that high mRNA levels of human concentrative nucleoside transporter 3 (hCNT3) in pre-F-ara-A treatment CLL samples correlated with clinical resistance to F-ara-A, with a shorter time to progression (TTP; hazard ratio, HR, 4.67; Po0.01) and decreased OR (11 vs 69%, P ¼ 0.002). 22 To further evaluate the importance of hCNT3 as a routine clinical predictive marker, in the present study we explored the value of immunohistochemistry (IHC) for the hCNT3 protein as a marker of F-ara-A resistance in CLL.…”
mentioning
confidence: 99%
“…In fact, decreased nucleoside transporter expression has been shown to be correlated to decreased response to deoxynucleoside analogue-based treatment. [93][94][95] …”
Section: New Systems and Perspectivesmentioning
confidence: 99%